2015
DOI: 10.1364/boe.6.001055
|View full text |Cite
|
Sign up to set email alerts
|

Label-free nonlinear optical imaging of mouse retina

Abstract: A nonlinear optical (NLO) microscopy system integrating stimulated Raman scattering (SRS), two-photon excited fluorescence (TPEF) and second-harmonic generation (SHG) was developed to image fresh mouse retinas. The morphological and functional details of various retinal layers were revealed by the endogenous NLO signals. Particularly, high resolution label-free imaging of retinal neurons and nerve fibers in the ganglion cell and nerve fiber layers was achieved by capturing endogenous SRS and TPEF signals. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…Over the past decades, the ORR has been widely used as an intrinsic indicator of redox states in cells and tissues [26][27][28]. In addition to redox ratio imaging, fluorescence lifetime imaging microscopy (FLIM) has also been used for mapping of cellular metabolism [29][30][31] and detection of pathogens [32]. We found that the ORR of BAT increases significantly after NE injection in mice, which is correlated with the temperature rise in BAT induced by thermogenesis [14].…”
Section: Introductionmentioning
confidence: 87%
“…Over the past decades, the ORR has been widely used as an intrinsic indicator of redox states in cells and tissues [26][27][28]. In addition to redox ratio imaging, fluorescence lifetime imaging microscopy (FLIM) has also been used for mapping of cellular metabolism [29][30][31] and detection of pathogens [32]. We found that the ORR of BAT increases significantly after NE injection in mice, which is correlated with the temperature rise in BAT induced by thermogenesis [14].…”
Section: Introductionmentioning
confidence: 87%
“…Details of the integrated multimodal NLO microscopy system used in this work have been described in our previous study [21]. Briefly, in SRS imaging, portion of a femtosecond Ti:sapphire laser of 140 fs pulse duration (Chameleon Ultra II, Coherent, Santa Clara, CA) tuned at 830 nm was used as the pump beam.…”
Section: Multimodal Nlo Microscope Systemmentioning
confidence: 99%
“…1. Nonlinear optical (NLO) microscopy provides an ideal solution to resolve the structural characteristics in tissues and cells, featured with its inherent 3D resolution and capacity for deep penetration [19][20][21]. Recently, NLO microscopy has been used to study the chondrocytes and ECM of cartilage [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Fiber lasers require no water-cooling, are less sensitive to air currents or changes in temperature, and their applications to three-photon processes are above the DNA damaging UV regime. While Ti: sapphire lasers have been used for multiphoton microscopy of the retina, 14 their third-harmonic is centered at 266 nm, which matches the absorption maximum of DNA. By establishing the native multiphoton signals that arise from wild type ex vivo retinas, in vivo and clinical use for the diagnosis and treatment of retinal diseases, such as age-related macular degeneration (AMD) can be established.…”
Section: Introductionmentioning
confidence: 99%